Mach Zehnder Inferometer using Plasmonic Waveguides - Nishi.G.N, Viswas.S.Nair (International Journal of Advanced Science and Technology, 2020)
MZI devices have been designed with the conventional plasmonic waveguides. The effective refractive index of each waveguides has been found and the phase difference induced by them has been analyzed and calculated .The MZI was initially designed using the conventional inorganic material which is Lithium Niobate with an electro-optic coefficient of 30 pm/V.Later the material was replaced with the new organic electro-optic polymers like JRD1, DLD164, CLD1.The electro-optic coefficient of these organic materials are 193pm/V, 180pm/V, 90pm/V respectively which is much higher than the usual inorganic material. The various parameters of the modulators such as change in refractive index, half-wave voltage, figure-of-merit etc. has been determined using various inorganic and organic polymers. It has been found that modulators using organic polymers have better performance compared to the conventional Lithium Niobate modulators.